Did monkeys invent the monkey wrench? Hardware stores and hardware stories - Vince Staten (New York Simon & Schuster, 1996)
Is the Swiss Army Knife Swiss? What feats of imagination went into inventing the Vise-Grip, the reciprocating saw, the Weed Eater? In this charming romp through hardware stores and lore, Vince Staten uncovers the secret history of the things that hold a house together and hold many people in thrall. Illustrations.
Keywords: Winfield Hardware.Hardware industry -- West Virginia -- Winfield -- Anecdotes.Hardware stores -- West Virginia -- Winfield.Winfield (W. Va.) -- Social life and customs.Hardware industry.Hardware stores.Manners and customs.West Virginia -- Winfield